Alcohol gas sensor of atomic-scale transition metal iridium doped indium oxide

By fabricating an ethanol gas sensor using atomically iridium-doped indium oxide material, the problems of slow response, high cost, non-specific selectivity, and insufficient sensitivity of traditional ethanol gas sensors have been solved, achieving efficient, low-cost, and stable ethanol detection, which is suitable for industrial and environmental monitoring.

CN120948565APending Publication Date: 2025-11-14NORTHEAST FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511223336.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-29
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Traditional ethanol gas sensors suffer from drawbacks such as slow response, high cost, non-specific selectivity, insufficient sensitivity, and high minimum detection limit. Furthermore, in traditional doping methods, atoms tend to agglomerate, and the utilization rate of doped atoms within the material is not high.

Method used

An atomic-level transition metal iridium-doped indium oxide material was prepared by precipitation. By coating the iridium-doped indium oxide material onto a ceramic tube and using a Ni-Gr alloy heating wire combined with a gold electrode, an ethanol gas sensor was formed.

Benefits of technology

It achieves rapid, specific, efficient and stable detection of ethanol gas, with high sensitivity, a detection limit at the ppm level, low material cost, and an environmentally friendly synthesis process, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120948565A_ABST
    Figure CN120948565A_ABST
Patent Text Reader

Abstract

The invention discloses an atomic-scale transition metal iridium doped indium oxide ethanol gas sensor, and relates to an ethanol gas sensor. The invention aims to solve the problems that atoms are easy to agglomerate and the utilization rate of doped atoms in a material is not high in a traditional doping mode. After indium oxide and a chloroiridic acid solution are uniformly mixed, the monatomic iridium doped indium oxide nano sensitive material is obtained through an impregnation method. The surface of a ceramic tube of the sensor is a coating prepared from an indium oxide nano sensitive material doped with monatomic iridium, and a gold-plated pin on the ceramic tube is used for measuring a signal. The sensor provided by the invention has the advantages of high sensitivity, low detection lower limit, short recovery time and very good selectivity and repeatability. The method is applied to detection of nitrogen dioxide in the atmospheric environment. The preparation process is simple, the size is small, the stability is good, safety and harmlessness are achieved, and the important application value is achieved. The invention belongs to the technical field of gas sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an ethanol gas sensor, belonging to the field of gas sensor technology. Background Technology

[0002] Gas sensors are invaluable in disease diagnosis, environmental monitoring, food safety, and extreme environments (such as polar regions, deep seas, and outer space). However, traditional devices still face challenges such as low sensitivity, slow response, baseline drift, and high-temperature operation. In recent years, semiconductor resistive sensors have become a research hotspot due to their advantages of high sensitivity, low cost, and easy integration. The performance of the sensitive material directly determines its final performance. Single-atom catalysts, with their atomically dispersed metal sites, can maximize the utilization of precious metals, reduce reaction energy barriers, and significantly improve selectivity, and are considered a new approach to overcome the bottlenecks of traditional nanomaterials. Their catalytic behavior is highly similar to the gas-solid interface reaction in gas sensing processes, thus holding promise for achieving high-sensitivity, low-temperature, and rapid detection of trace gases by enhancing gas adsorption-activation-electron transfer efficiency.

[0003] Indium oxide (IO), a typical environmentally friendly n-type semiconductor metal oxide material, has attracted much attention in related fields due to its rapid detection response, low detection cost, and convenient operation. Its crystal structure is cubic ferromanganese oxide (CFA), with a band gap of approximately 2.8–3.6 eV, and it also exhibits high carrier mobility (~10–160 cm⁻¹). 2 With its high concentration ( / V·s) and excellent chemical stability, ethanol is an ideal candidate material to replace traditional heavy metal oxides (such as SnO2 and ZnO). Industrially, ethanol is a commonly used raw material; its vapor is flammable and explosive. Real-time concentration monitoring can provide early warning of dangers, prevent explosions, and ensure production safety. In environmental monitoring, large amounts of ethanol emissions participate in atmospheric reactions, affecting air quality; detection can assist in the formulation of environmental policies. In the medical field, detection can ensure the air quality in the workplace and prevent the harm caused by excessively high ethanol concentrations. Ethanol gas detection plays a crucial role in ensuring industrial safety, environmental protection, and medical health.

[0004] In fact, research on ethanol gas sensors has been continuously deepening over the past few years, and semiconductor gas sensors (zinc oxide, ferric oxide, tungsten oxide, etc.) and hybrid potential gas sensors (zinc oxide / graphene and bismuth tungstate / reduced graphene oxide, etc.) have been developed. However, traditional ethanol metal oxide semiconductor gas sensors suffer from drawbacks such as long response time, high cost, non-specific selectivity, insufficient sensitivity, and a need to reduce the minimum detection limit. Therefore, it is crucial to propose an ethanol gas sensor with single-atom doped metal oxide semiconductor nanomaterials to address these issues. Summary of the Invention

[0005] To address the problems of easy agglomeration of atoms and low utilization rate of doped atoms in traditional doping methods, this invention proposes an atomic-level transition metal iridium-doped indium oxide ethanol gas sensor.

[0006] The technical solution adopted by the present invention to solve the above problems is as follows: The present invention includes a ceramic tube coated with iridium-doped indium oxide material, and an alloy heating wire is provided inside the ceramic tube, with gold electrodes connected to both ends of the alloy heating wire.

[0007] Furthermore, the ceramic tube is an Al2O3 ceramic tube, and the alloy heating wire is a Ni-Gr alloy heating wire.

[0008] Furthermore, the preparation method of iridium-doped indium oxide material is as follows:

[0009] Step 1: Weigh out indium nitrate;

[0010] Step 2: Dissolve indium nitrate in a mixed solution of deionized water and ethanol, stir continuously and add ammonia water to obtain a suspension;

[0011] Step 3: Stir the suspension obtained in Step 2 under heating conditions;

[0012] Step 4: After washing and drying the white solid obtained from the reaction, transfer it to a muffle furnace for calcination to obtain indium oxide solid powder;

[0013] Step 5: Weigh out indium oxide and chloroiridic acid for later use;

[0014] Step 6: Dissolve the weighed indium oxide and chloroiridium acid in deionized water and stir under heating conditions;

[0015] Step 7: After washing and drying the white solid obtained from the reaction, transfer it to a muffle furnace for calcination to obtain iridium-doped indium oxide solid powder.

[0016] Furthermore, the mass of indium nitrate weighed in step 1 is 5–15 g.

[0017] Furthermore, in step 2, the volume of deionized water is 10 mL to 100 mL, the volume of ethanol is 100 to 200 mL, and the volume of ammonia is 10 to 100 mL.

[0018] Furthermore, in step 3, the heating temperature is 10–150°C, and the stirring time is no less than 5 hours.

[0019] Furthermore, in step 4, the working temperature of the muffle furnace is 400℃~600℃, the working time is not less than 1 hour, and the heating rate is 2~10℃ / min.

[0020] Furthermore, in step 5, the mass ratio of indium nitrate to chloroiridium acid is 1:(0.1~1).

[0021] Furthermore, in step 6, the heating temperature is 10–150°C, and the stirring time is no less than 10 hours.

[0022] Furthermore, in step 7, the working temperature of the muffle furnace is 200℃~500℃, the working time is not less than 3 hours, and the heating rate is 2~10℃ / min.

[0023] The beneficial effects of this invention are as follows: This invention employs a precipitation method, using indium nitrate nanoparticles as the indium source, to successfully prepare an atomically uniformly dispersed iridium-doped oxide material, overcoming the drawbacks of traditional doping methods such as easy agglomeration of atoms and low utilization rate of doped atoms within the material. Iridium doping not only increases the number of oxygen vacancies in the material but also enhances its oxygen adsorption capacity. Therefore, with its high utilization rate and abundant active sites, the gas-sensing performance of the material is significantly improved, enabling the preparation of rapid, specific, efficient, stable, non-toxic, and low-cost gas detection materials. In some test examples of this invention, the ethanol gas sensor prepared using the gas-sensing material of this invention achieved a response value of 75 for 100 ppm ethanol at 220°C.

[0024] The side-heated nitrogen dioxide gas sensor based on single-atom iridium-doped indium oxide nanomaterial prepared in this invention has the following advantages:

[0025] This invention utilizes a precipitation method to prepare a uniformly dispersed, atomically-level iridium-doped oxide material using indium nitrate nanoparticles as the indium source. Unlike traditional doping methods that suffer from dopant agglomeration and low utilization of dopant atoms within the material, this method achieves high utilization and a large number of active sites, significantly improving the gas-sensing properties of the material.

[0026] The nano-sensitive material prepared by this invention has the advantages of good repeatability, short response time, high selectivity and sensitivity, and the detection limit of the sensor can reach the ppm level, enabling long-term and stable use.

[0027] The side-heated nitrogen dioxide gas sensor prepared by this invention using a single-atom iridium-doped indium oxide nanomaterial has a simple fabrication process, low material cost, and a green and environmentally friendly synthesis route, making it suitable for industrial production. Attached Figure Description

[0028] Figure 1 (a) is a schematic diagram of the planar structure of the nitrogen dioxide gas sensor based on iridium-doped indium oxide nanomaterial prepared in this invention.

[0029] Figure 1 (b) is a SEM image of the iridium-doped indium oxide nanosensor material prepared in this invention;

[0030] Figure 1(c) is a map of iridium element distribution based on iridium-doped indium oxide nanosensitive material prepared in this invention;

[0031] Figure 2 (a) is a TEM image of the iridium-doped indium oxide nanosensitive material prepared in this invention;

[0032] Figure 2 (b) is a STEM image of the iridium-doped indium oxide nanosensor material prepared in this invention;

[0033] Figure 2 (c) is an HRTEM image of the iridium-doped indium oxide nanosensor material prepared in this invention;

[0034] Figure 2 (d) shows the XRD patterns of the iridium-doped indium oxide nanosensitive material (example) and the indium oxide nanosensitive material (comparative example) prepared in this invention;

[0035] Figure 3 This is a selectivity chart of 100 ppm for different gases at 220°C for the comparative examples and embodiments described in this invention.

[0036] Figure 4 These are the response curves of the comparative example and the embodiment to 100 ppm ethanol gas at 120℃-280℃.

[0037] Figure 5 The concentration gradient of 1ppm-500ppm ethanol atmosphere was measured at 220°C for the comparative and examples.

[0038] Figure 6 The example shows the response recovery time curve of 100 ppm ethanol gas at 220°C.

[0039] Figure 7 This is a long-term stability graph of the comparative example and the embodiment measured at 220°C for 30 days;

[0040] Figure 8 (a) is a schematic diagram showing the breakage of the OO bonds in the comparative and example samples due to oxygen adsorption;

[0041] Figure 8 (b) is a schematic diagram of the optimized structure of the proportions and embodiments;

[0042] Figure 8 (c) Schematic diagram of the adsorption energy of oxygen, the binding energy of O, and the dissociation energy of oxygen;

[0043] Figure 8 (d) is the net spin density of *O displayed on the isosurface as [value missing]. Schematic diagram;

[0044] Figure 1 In the middle, 1-gold electrode, 2-ceramic tube, 3-alloy heating wire. Example

[0045] An atomically-level transition metal iridium-doped indium oxide ethanol gas sensor includes a ceramic tube and a hexagonal socket. The ceramic tube structure consists of a tubular sensing element and four electrode pins soldered to the hexagonal socket. Additionally, a nickel-chromium alloy coil passes through the tubular sensing element and is soldered to two other terminals of the hexagonal socket. The tubular sensing element is made of alumina (Al₂O₃)-based ceramic and has gold electrodes at both ends. The sensor is characterized by transmitting the resistance signal of the sensing material to a Fluke meter through the hexagonal socket. The surface of the tubular sensing element is coated with a metal-organic framework-derived copper-doped zinc stannate nanomaterial prepared by the following method.

[0046] Comparative example:

[0047] The fabrication process of indium oxide nanomaterials for a heated ethanol gas sensor is as follows:

[0048] Step 1. Preparation of indium oxide solid: Mix 12.2 g indium nitrate, 50 mL deionized water, and 140 mL ethanol, and stir thoroughly until dissolved. Then add 35 mL ammonia and 110 mL ethanol to the mixture, and stir at 80 °C for 4 h. The resulting product is then washed alternately by centrifugation with water and anhydrous ethanol to obtain a white solid.

[0049] Step 2. Preparation of indium oxide powder: The solid obtained in step 1 was dried at 80°C for 24 hours, then heated to 500°C in a muffle furnace at a rate of 2°C / min and held for 3 hours, and then cooled naturally to obtain indium oxide powder.

[0050] Step 3. Preparation of indium oxide nanomaterial-based heated nitrogen dioxide gas sensor: After the indium oxide nanomaterial is taken out, it is made into a suspension with ethanol and uniformly coated on the tubular sensing element at room temperature. Then, it is heated to 200℃ in a muffle furnace at a rate of 2℃ / min and calcined again for 2h. The nickel-chromium alloy coil is inserted into the tubular sensing element after the above treatment, and then spot-welded to a hexagonal tube base. It is then aged for 3-5 days using an aging bench to obtain the heated ethanol gas sensor based on indium oxide nanomaterial.

[0051] Example:

[0052] The iridium-doped indium oxide nanomaterial was prepared, and a side-heated nitrogen dioxide gas sensor was fabricated using the iridium-doped indium oxide nanomaterial. The specific fabrication process is as follows:

[0053] Step 1. Preparation of solid indium oxide: Same as the comparative example.

[0054] Step 2. Preparation of indium oxide powder: Same as the comparative example.

[0055] Step 3. Preparation of iridium-doped indium oxide: Take 1 g of indium oxide powder and 0.32 g of chloroiridium acid and dilute with deionized water to 50 mL. Then stir at 50 °C for 12 h. Wash the obtained precipitate with deionized water. Dry the obtained solid at 80 °C for 24 h, then heat it to 300 °C in a muffle furnace at a rate of 2 °C / min and hold for 3 h, then let it cool naturally to obtain iridium-doped indium oxide powder.

[0056] Step 4. Fabrication of a heated nitrogen dioxide gas sensor using iridium-doped indium oxide nanomaterials: Same as the comparative example.

[0057] The indirect-heated sensor was connected to a Fluke multimeter signal tester via a clip. The sensors prepared in the comparative example and the embodiment were placed in air and 100ppm ethanol atmospheres respectively to test the resistance signal.

[0058] SEM images of the iridium-doped indium oxide nanomaterials prepared in this invention are shown below. Figure 1 As shown in (b), by Figure 1 (b) As shown in the figure, the prepared iridium-doped indium oxide nanosensitive material is a uniformly sized granular nanosensitive material; the iridium element distribution diagram of the iridium-doped indium oxide nanosensitive material prepared in this invention is as follows. Figure 1 As shown in (c), the image shows that the iridium element is uniformly dispersed in the material.

[0059] Figure 2 Figure (a) shows an example where the prepared iridium-doped indium oxide sensitive material is composed of uniform nanoparticles with no obvious agglomeration and good dispersibility; Figure (b) shows an example where the prepared iridium-doped indium oxide nanosensitive material is a STEM image. As can be seen from the figure, iridium atoms are highly dispersed in the form of single atoms and uniformly loaded on the surface of the indium oxide support. Figure 2 (c) shows the HRTEM image of the prepared iridium-doped indium oxide nanosensitive material in the example. The image shows clear lattice fringes, which confirms the crystal structure of the indium oxide matrix. Figure 2 As shown in (d), the XRD images of the prepared comparative examples and embodiments are shown in the figure. It can be seen from the figure that the comparative examples and embodiments are completely compared with the indium oxide card PDF#06-0416.

[0060] The comparative figures and examples show a comparison of the response values ​​of different gases at 220°C to 100 ppm. Figure 3 As shown. From Figure 3 As can be seen from the examples, the examples have good selectivity for 100 ppm ethanol.

[0061] The sensitivity of the comparative examples and embodiments to testing in a 100 ppm ethanol atmosphere at temperatures ranging from 120°C to 280°C is as follows: Figure 4 As shown. From Figure 4 As can be seen from the example, the highest response value, reaching 75, is achieved at 330°C.

[0062] The concentration gradient curves of ethanol from 1 ppm to 500 ppm at 220°C for the comparative examples and the examples are shown below. Figure 5 As shown. Response value test method: First, place the sensor in the gas cylinder, and measure the resistance at this time using a meter connected to the sensor. This gives the sensor's resistance value in air, i.e., R. a Then, using a syringe, ethanol ranging from 1 ppm to 500 ppm is injected into the gas cylinder, and the resistance value (R) of the sensor in ethanol at different concentrations is measured. g According to the definition of sensitivity S, S = R a / Rg was used to calculate the sensor sensitivity at different concentrations. The graph shows that the sensor sensitivity increases with increasing ethanol concentration.

[0063] The response time curve of the example to ethanol at 220°C is shown below. Figure 6 As shown, this material exhibits excellent response speed.

[0064] The long-term stability of the examples and comparative examples measured at 220°C for 30 days is as follows: Figure 7 As shown, this material exhibits good stability.

[0065] Comparative examples and optimized structures, such as Figure 8 (a) and 8(b) are shown on the left and in the middle, the configuration of oxygen facing the oxygen vacancy is shown. The oxygen adsorption energies of the two are similar, and the comparative example shows that the surface oxygen stability is slightly stronger. Considering the oxygen anion pathway reaction, the oxygen dissociation behavior of the comparative example and the example is studied. Figure 8 (a) and 8(b) (right side), it was found that the oxygen dissociation energy in the examples was much smaller than that in the comparative example, confirming that iridium is the key site promoting oxygen dissociation and can "activate" oxygen molecules. Furthermore, the oxygen binding energy in the examples was more negative, indicating a stronger interaction with oxygen. Spin density calculations for the comparative and examples ( Figure 8 (d) indicates that the surface *O atoms of the embodiment are more reactive, and their high spin state is conducive to the breaking of CH bonds in ethanol, accelerating the oxidation to carbon dioxide and water.

[0066] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent substitutions, and improvements made to the above embodiments without departing from the scope of the present invention, based on the technical essence of the present invention and within the spirit and principles of the present invention, shall still fall within the protection scope of the present invention.

Claims

1. An atomically-level transition metal iridium-doped indium oxide ethanol gas sensor, characterized in that, It includes a ceramic tube (2), which is coated with iridium-doped indium oxide material. An alloy heating wire (3) is provided inside the ceramic tube (2), and gold electrodes (1) are connected to both ends of the alloy heating wire (3).

2. The atomic-level transition metal iridium-doped indium oxide ethanol gas sensor according to claim 1, characterized in that, The ceramic tube (2) is an Al2O3 ceramic tube, and the alloy heating wire (3) is a Ni-Gr alloy heating wire.

3. The atomic-level transition metal iridium-doped indium oxide ethanol gas sensor according to claim 1, characterized in that, The preparation method of iridium-doped indium oxide material is as follows: Step 1: Weigh out indium nitrate; Step 2: Dissolve indium nitrate in a mixed solution of deionized water and ethanol, stir continuously and add ammonia water to obtain a suspension; Step 3: Stir the suspension obtained in Step 2 under heating conditions; Step 4: After washing and drying the white solid obtained from the reaction, transfer it to a muffle furnace for calcination to obtain indium oxide solid powder; Step 5: Weigh out indium oxide and chloroiridic acid for later use; Step 6: Dissolve the weighed indium oxide and chloroiridium acid in deionized water and stir under heating conditions; Step 7: After washing and drying the white solid obtained from the reaction, transfer it to a muffle furnace for calcination to obtain iridium-doped indium oxide solid powder.

4. The atomic-level transition metal iridium-doped indium oxide ethanol gas sensor according to claim 3, characterized in that, The mass of indium nitrate weighed in step 1 is 5-15g.

5. The atomic-level transition metal iridium-doped indium oxide ethanol gas sensor according to claim 3, characterized in that, In step 2, the volume of deionized water is 10 mL to 100 mL, the volume of ethanol is 100 to 200 mL, and the volume of ammonia is 10 to 100 mL.

6. The atomic-level transition metal iridium-doped indium oxide ethanol gas sensor according to claim 3, characterized in that, In step 3, the heating temperature is 10-150℃, and the stirring time is no less than 5 hours.

7. The atomic-level transition metal iridium-doped indium oxide ethanol gas sensor according to claim 3, characterized in that, In step 4, the working temperature of the muffle furnace is 400℃~600℃, the working time is not less than 1 hour, and the heating rate is 2~10℃ / min.

8. An atomic-level transition metal iridium-doped indium oxide ethanol gas sensor according to claim 3, characterized in that, The mass ratio of indium nitrate and chloroiridium acid weighed in step 5 is 1:(0.1~1).

9. An atomic-level transition metal iridium-doped indium oxide ethanol gas sensor according to claim 3, characterized in that, In step 6, the heating temperature is 10-150℃, and the stirring time is no less than 10 hours.

10. An atomic-level transition metal iridium-doped indium oxide ethanol gas sensor according to claim 3, characterized in that, In step 7, the working temperature of the muffle furnace is 200℃~500℃, the working time is not less than 3 hours, and the heating rate is 2~10℃ / min.

Citation Information

Patent Citations

  • M / ZrO2-In2O3 monatomic catalyst as well as preparation method and application thereof

    CN120132841A

  • A gas sensor of metaloxide including catalyst and a fbrication method thereof

    KR1020100008550A